Jamestown Canyon Virus Seroprevalence in Endemic Regions and Implications for Diagnostic Testing - Sutter, Rebekah A; Calvert, Amanda E; Grimm, Kacie; Biggerstaff, Brad J; Thrasher, Elisa; Mossel, Eric C; Martin, Stacey W; Lehman, Jennifer; Saa, Paula; Townsend, Rebecca; Krysztof, David; Brown, Catherine M; et al. (Clinical infectious diseases, 2025)
Jamestown Canyon virus, a mosquito-borne virus, can cause asymptomatic infection, febrile illness, or neuroinvasive disease in humans. Previous studies have found Jamestown Canyon virus-specific antibodies in a 4%-54% of people in various U.S. regions. To understand baseline seroprevalence in regions with the highest number of reported disease cases, we performed a serosurvey among blood donors. We randomly selected blood donation specimens collected during December 2019-April 2020 from residents of counties reporting ≥2 disease cases in 2019 or 1 case in 2019 and ≥1 case during 2010-2018. Specimens were screened for Jamestown Canyon virus-specific neutralizing antibodies and, if positive, tested for immunoglobulin M (IgM) antibodies. We estimated county population seroprevalence by calibrating sample weights to population census data. Fourteen counties in 3 states, Massachusetts, Minnesota, and Wisconsin, met the inclusion criteria. Within each state, average county seroprevalence ranged from 16.8% (95% confidence interval [CI], 9.3-27.0) to 18.8% (95% CI, 14.0-24.4) for Jamestown Canyon virus-neutralizing antibodies and from 7.6% (95% CI, 4.2-12.5) to 13.5% (95% CI, 9.6-18.3) for both neutralizing and IgM antibodies. Estimated Jamestown Canyon virus seroprevalence, including for IgM antibodies, is elevated in endemic areas, complicating the interpretation of serologic testing in diagnosing acute disease in symptomatic individuals. Diagnosing Jamestown Canyon virus disease requires a high degree of clinical suspicion, ruling out other possible causes of illness, and if possible, collecting acute and convalescent samples. New assays to detect acute infection could improve diagnosis and public health surveillance for Jamestown Canyon virus disease.